Recycled Coarse Aggregate for Sustainable Self-Compacting Concrete and Mortar - Syed Ali Rizwan; Muhammad Irfan-ul-Hassan; Abdur Rahim; Salman Ali; Asim Sultan; Deprizon Syamsunur; Nur Izzi Md Yusoff (Advances in Materials Science and Engineering)
The utilization of construction and demolition waste is useful for sustainable infrastructure development and protecting the environment. In this research, the properties of self-compacting concrete produced by replacing the natural coarse aggregates (NCA) with inferior recycled coarse aggregates (RCA) were investigated. The properties of self-compacting concrete (SCC) and self-compacting mortar (SCM) with varying replacements of RCA (0, 25, 50, and 100%) in NCA were determined. The flow, strength, early shrinkage tests, and microstructure using X-ray diffraction (XRD) and a scanning electron microscope (SEM) were investigated. The fresh property results indicated that the viscosity of freshly mixed SCC increased with higher replacement levels of RCA, thus reducing flow. The compressive strength of RCA SCC was reduced up to 30% for a 100% replacement level, while the flexural strength was reduced by about 15%. The compressive strength and flexural strength of SCMs, however, increased up to 12% and 28% for 100% replacement with RCA. The mechanical strength of SCM increases with RCA because of high fine content which reduces the porosity and makes the system denser. The early age linear shrinkage increases with RCA due to its greater water absorption. The results indicate that recycled coarse aggregate can be effectively used as the replacement of NCA in SCC to produce sustainable and eco-friendly structural concrete.